Transforming the Ledger through the Evolving Role of Artificial Intelligence in the Accounting Profession - Iyere Samuel Iheonkhan (International Journal of Science and Society (IJSS), 2026)
The rapid advancement of artificial intelligence (AI) has significantly transformed the accounting profession by changing traditional accounting processes and professional responsibilities. This study aims to examine the evolving role of AI in accounting practices, particularly in financial accounting, management accounting, and auditing. The study employed a structured literature review approach using peer-reviewed articles indexed in the Scopus database published between 2019 and 2023. Relevant studies were identified, screened, and analyzed systematically to evaluate the impact of AI technologies on accounting functions. The findings reveal that AI improves operational efficiency through the automation of repetitive tasks such as bookkeeping, transaction processing, reconciliation, and financial reporting. AI technologies also strengthen analytical capabilities by supporting predictive analytics, risk assessment, fraud detection, and strategic decision-making processes. In addition, the integration of AI has shifted the role of accountants from routine administrative activities toward higher-value functions including advisory services, business analysis, and strategic planning. The study concludes that AI is not replacing accountants entirely but rather reshaping the profession by enhancing productivity, accuracy, and decision-making quality. The study recommends that accounting professionals, educational institutions, and organizations invest in digital competencies, AI training, and technological adaptation to remain competitive in the evolving business environment. The implications of this study highlight the necessity for continuous professional development and the integration of AI-related competencies into accounting education and professional practice.